Abu al-Rabi’ Zaidah al-Qaysi al-Bakri (early third century AH) and his linguistic narrations. - Kamel, Dr. Qassim Mohmmed (Thi Qar Arts Journal, 2024)
Zaida Al - Bakri, unknown narrator , lived in The era linguistic novel , between The meddle of The second centuries and the third Hijri year, he was not shed light and passed by whoever mentioned it in passing, our attention was drawn to the presence of his narratives have reached us in the comments in a book Al - Ain , as well as others we found in Tahtheab alloga . M, which reflects the value of the narrator and his narratives which is what made us To collect and study it to save whet is related to his nickname his title , the length of time he lived , and the most important aspects linguistically , in his over-80s , we go astray .